Two Letters of Marsilio Ficino and Their Translations in Humanistic Bohemia - Nejeschleba, Tomáš (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2021)
Two of Marsilio Ficino’s letters among his correspondence—the letter De officiis and the letter Veritas de institutione principis—enjoyed heightened popularity in the sixteenth century. One of the first translations of Ficino into the vernacular is a translation of these two letters into Czech, printed in Prague around the year 1500. Czech humanist Řehoř Hrubý of Jelení (ca. 1460–1514) seems to be a plausible candidate for the authorship. The second translation into Czech was published in 1520 by Oldřich Velenský of Mnichov (1495–1531). This article examines the Czech humanistic translations of Ficino’s letters and places them into the context of the Czech humanistic movement at the beginning of the sixteenth century, which emphasized moral topics from Italian Renaissance Platonism. It argues that these letters from Ficino supported the moral claims of Czech pre-Reformation and Reformation thought at the beginning of the sixteenth century.